2010
DOI: 10.4021/jocmr474w
|View full text |Cite
|
Sign up to set email alerts
|

Intratesticular Epidermoid Cyst: A Rare Tumor

Abstract: Testicular epidermoid cyst is extremely rare injury, which in recent studies has been regarded as a tumor. Some authors consider this lesion as a cystic monodermal teratoma, the histogenesis remains controversial. In this study we provide clinical and morphological characteristics of an epidermoid cyst in the left testicle in a 16 years old patient, where apparently a nodular lesion in the left testicle was detected.KeywordsCyst; Epidermoid; Intratesticular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Some investigators consider it a nonneoplastic entity, while others regard it as a monodermal teratoma [4]. Pediatric examples of epidermoid cyst are uncommon [59].…”
Section: Germ Cell Tumorsmentioning
confidence: 99%
“…Some investigators consider it a nonneoplastic entity, while others regard it as a monodermal teratoma [4]. Pediatric examples of epidermoid cyst are uncommon [59].…”
Section: Germ Cell Tumorsmentioning
confidence: 99%
“…5 TEC is a rare benign lesion, with controversial histological origins. Some studies reported that these tumours derive from germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of vascularity in the cyst helps radiologists to distinguish epidermoid cysts from testicular malignant tumours. 5,6 A number of studies have reported the value of magnetic resonance imaging (MRI) in the diagnosis of TEC. Based on these studies, TEC may appear at MRI as concentric rings of low and high signal intensity on T1 and T2 weighted images or a peripheral rim with low signal intensity on both T1 and T2 weighted images.…”
Section: Discussionmentioning
confidence: 99%